EFEKTIVITAS PERATURAN DAERAH NOMOR 3 TAHUN 2018 TERHADAP PARKIR LIAR DI KOTA SURABAYA - Ifan Wahyu Satria Martin; Lucky Hergiantoro Saputra; Mochamad Laksana Bintang; Gheogita Wulandary (Fakultas Hukum Universitas Wiraraja, 2025)
As a metropolitan city and the center of government of East Java, Surabaya faces serious problems related to increasing illegal parking. Although Regional Regulation Number 3 of 2018 concerning Parking Implementation has been issued, illegal parking practices are still rampant in various places such as minimarkets, pharmacies, and sidewalks. This study uses normative legal methods to analyze the effectiveness of the regulation. The results show that the surge in the number of vehicles and the lack of official parking facilities are the main causes of the emergence of illegal parking. This practice is often carried out by unlicensed individuals, and the lack of law enforcement worsens the situation. Public views vary—some feel disadvantaged, but others sympathize with illegal parking attendants from the lower economic class. The lack of socialization of the Regional Regulation and the lack of officers in the field also hamper the effectiveness of this policy. The study recommends increasing the socialization of regulations, stricter law enforcement, the use of technology such as CCTV, and the addition of official parking areas. Public awareness to obey the rules also needs to be increased. With collaboration between the government, authorities, and the community, it is hoped that a more orderly and fair parking system will be created in Surabaya.